The Herbal Compound Thymol Protects Mice From Lethal Infection by Salmonella Typhimurium - Zhang, Yong; Liu, Yan; Qiu, Jiazhang; Luo, Zhao-Qing; Deng, Xuming (Frontiers in Microbiology, 2018)
Type III secretion system (T3SS) is an essential pathogenic determinant for many important bacterial pathogens; it functions to thwart immune defense by delivering effectors into host cells. Because of its essential role in bacterial virulence, this machinery is an important target in the development of novel anti-virulence therapeutics. By using an effector-lactamase fusion reporter, we identified thymol, a monoterpene phenol derivative of cymene, as an effective inhibitor of the T3SS-1 of Salmonella Typhimurium. Our results indicate that thymol effectively protected mice against S. Typhimurium-induced mortality and pathological damages, suggesting that this compound can be developed for the control of infections caused by Salmonella species.